Understanding and communicating deathwatch beetle activity on HMS Victory - Harvey, Cathryn (Cranfield University, 2024)
3MT contribution to the Defence and Security Doctoral Symposium 2023
Keywords: DSDS23; DSDS23 3MT; Deathwatch beetles; heritage conservation policy; Deathwatch; Conservation; HMS Victory; Entomology; Heritage science